The effects of supplementation with selected browse plants on feed intake, production and composition of milk in lactating Katjang-cross goats - Baba, A.S.H.; Noraida, I.; Sembiring, M. (2000)
The effect of inclusion of browse material (tree leaves) on the lactation performance of Katjang-cross dairy goats was investigated. Goats were offered either a basal diet of napier grass ad libitum plus concentrate (NC) or the basal diet supplemented with tree leaves (Leuceana leucocephala, Artocarpus heterophyllus and Melastroma marabathricum (NCB). Average dry matter and water intakes were 32% and 20% respectively higher in the browse supplemented group compared to the control group. The length of lactation period was longer for browse supplemented animals (16 weeks) than those for animals fed the basal diet alone (12 weeks). Goats in the browse supplemented group yielded more milk (P<0.05) than those in the control group at both mid and late stages of lactation. Average daily milk yield in both groups was highest (P<0.01) in mid lactation but decreased during late lactation to a level below that seen in early lactation. Milk fat and protein contents were higher in the browse supplemented group (P<0.01) but the protein:fat ratio was not significantly different between groups (P>0.05). Selected browse plants may be used effectively to increase and sustain the productivity and quality of milk produced from goats fed with napier grass and palm-based concentrate.